Ancient Greece and the Olympics - Osborne, Mary Pope and Boyce, Natalie Pope (New York Random House, 2004)
Magic Tree House Research Guides are now Magic Tree House Fact Trackers! Track the facts with Jack and Annie!? When Jack and Annie got back from their adventure in?Magic Tree House #16: Hour of the Olympics,?they had lots of questions. What did the ancient Greeks wear? What did they do for fun? Where were the very first Olympics held? How are our modern Olympics similar to the ancient Olympics? Find out the answers to these questions and more as Jack and Annie track the facts. Filled with up-to-date information, photos, illustrations, and fun tidbits from Jack and Annie, the Magic Tree House Fact Trackers are the perfect way for kids to find out more about the topics they discovered in their favorite Magic Tree House adventures.
Include Illustrations
Keywords: Olympic games (Ancient) -- Greece